Carbon Tax Research Trend - Bima, Muhammad; Setiawati, Rhisma Indah; Agustin, Dwi Apriliana; Djasuli, Mohamad (Ilomata International Journal of Tax and Accounting, 2024)
This research focuses on mapping articles that discuss carbon tax published through sinta 1 and 2 accredited journals and scopus quartile 1 and 2. The purpose of this research is to explore more deeply about carbon tax research with a focus on business management and accounting in the 2015-2023 period. The method used in this research is a quantitative method with a bibliometric approach. This bibliometric approach is used to determine the development of research topics related to carbon tax research trends. Research samples, journal names, publication years, research methods, types of research variables and research data sources are the basis for mapping in this study. This research also visualizes carbon tax keywords using VOSviewer software. The results found that the search for articles that discuss carbon tax research found 8 articles published from accredited journals Sinta 1 and Sinta 2 and 50 articles from journals indexed by Scopus quartile 1 (Q1) and quartile (Q2) . This study contributes to knowing the trend of scientific publications on carbon tax, and provides an opening for researchers in conducting future research by conducting deeper calculations related to the amount of carbon emissions and carbon tax involving subjectivity in disclosure assessment.